ANALISIS DAMPAK PERPINDAHAN BANDAR UDARA TERHADAP PERTUMBUHAN PEREKONOMIAN DI KABUPATEN LOMBOK TENGAH - Lalu Muhammad Azmi Prasetya; Agus Suman (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this study is to analyze the impact of the existence of an airport on five sub- districts in Lombok Tengah regency that is Praya , Praya Barat , Praya Barat Daya ,  Praya Tengah , and Pujut .The impact of the displacement the airport includes central change growth and changes public welfare area around Lombok International Airport ( LIA). The method of analysis used was analysis   scallogram , centrality index, analysis of gravity, descriptive analysis. The analysis showed that a growth center near the area of the LIA is in Praya with in Praya Barat , Praya Barat Daya , Praya Tengah , and Pujut is the hinterland of Praya. Then the overall LIA positive impact on improving the welfare of the community around the LIA regardless of some problems inflicted .   Keywords: Growth Center, Scallogram, Centrality, Gravity, Public Welfare, Typology Klassen